Spray-Dried Polymeric Microspheres for Lipophilic Drugs: Formulation Design, Physicochemical Characterization, and In Vitro Release Evaluation - Felipe Nataren-Rodríguez; Jorge Pacheco-Molina; Sandra Leticia Gracia-Vásquez; Isaías Balderas-Rentería; Mónica A. Ramírez-Cabrera; Eder Arredondo-Espinoza; Karla J. Santamaría; Patricia González-Barranco (Pharmaceuticals)
Background/Objectives: The formulation of microspheres for lipophilic drugs using aqueous methods, such as spray drying, faces significant challenges. The main objective of this study was to evaluate the effect of the process parameters and polymer selection on the production of microspheres by spray drying for a lipophilic drug. Methods: Lipophilic drug-loaded microspheres were developed using various polymers via the aqueous spray drying method. The effects of the factors on the yield percentage and encapsulation efficiency were analyzed. Microspheres preparation included Agave inulin, guar gum, hydroxypropyl methylcellulose, and Eudragit® S100. A 23 factorial design was performed, and the parameters were optimized. Results: Inlet temperature, feed flow, and polymer percentage showed a significant effect (p < 0.05) on the yield percentage of guar gum microspheres and encapsulation efficiency of the inulin microspheres. Inulin and guar gum microspheres showed the best yield percentage (75.41%) and encapsulation efficiency (100%), respectively. In addition, guar gum microspheres had the best morphology, and hydroxypropyl methylcellulose microspheres were smaller and had an irregular surface. Eudragit did not maintain its delayed release property due to limitations of the aqueous method; inulin released the drug immediately, and guar gum and hydroxypropyl methylcellulose microspheres prolonged release only by a few additional hours. Conclusions: The experimental design showed that optimizing the parameters (inlet temperature, feed flow, and the type and percentage of polymer) can regulate the microsphere development process to obtain improved product yield and encapsulation efficiency results.